Internally reporting risk in financial services: an empirical analysis - Bryce, Cormac; Chmura, Thorsten; Webb, Robert; Stiebale, Joel; Cheevers, Carly (Springer, 2017)
The enduring failure of financial institutions to identify and deal with risk events continues to have serious repercussions, whether in the form of small but significant losses or major and potentially far-reaching scandals. Using a mixed-methods approach that combines an innovative version of the classic dictator game to inform prosocial tendencies with the survey based Theory of Planned Behaviour, we examine the risk-escalation behaviour of individuals within a large financial institution. We discover evidence of purely selfish behaviour that explains the lack significance in pressure to adhere to the subjective norms of colleagues around intention to report risks. A finding that has potentially important implications for efforts to instil a high-error management climate and incentivise risk reporting within organisations where risk, if ignored or unchecked, could ultimately have consequences that extend far beyond the institutions themselves.